Deaths from acute abdominal conditions and geographic access to surgical care in India: a nationally representative population-based spatial analysis. (27th April 2015) - Ng-Kamstra, Joshua S; Dare, Anna J; Patra, Jayadeep; Fu, Sze Hang; Rodriguez, Peter S; Hsiao, Marvin; Jotkar, Raju M; Thakur, J S; Sheth, Jay K; Jha, Prabhat; ,
Abstract: Background: Acute abdominal conditions have high case-fatality rates in the absence of timely surgical care. In India, and many other low-income and middle-income countries, few population-based studies have quantified mortality from surgical conditions and related mortality to access to surgical care. We aimed to describe the spatial and socioeconomic distributions of deaths from acute abdomen (DAA) in India and to quantify potential access to surgical facilities in relation to such deaths. Methods: We examined deaths from acute abdominal conditions within a nationally representative, population-based mortality survey of 1·1 million Indian households and linked these to nationally representative facility data. Spatial clustering of deaths from acute abdominal conditions was calculated with the Getis-Ord Gi* statistic from about 4000 postal codes. We compared high or low acute abdominal mortality clusters for their geographic access to well-resourced surgical care (24 h surgical and anaesthesia services, blood bank, critical care beds, basic laboratory, and radiology). Findings: 923 (1·1%) of 86 806 study deaths in those aged 0–69 years were identified as deaths from acute abdominal conditions, corresponding to an estimated 72 000 deaths nationally in India in 2010. Most deaths occurred at home (71%), in rural areas (87%), and were caused by peptic ulcer disease (79%). There was wide variation in rates of deaths from acute abdominal conditions. We identified 393 high-mortality geographic clusters and 567 low-mortality clusters. High-mortality clusters of acute abdominal conditions were located significantly further from well-resourced hospitals than were low-mortality clusters. The odds ratio of a postal code area being a high-mortality cluster was 4·4 (99% CI 3·2–6·0) for living 50 km or more from well-resourced district hospitals (rising to an OR of 16·1 for >100 km), after adjustment for socioeconomic status and caste. Interpretation: Improvements in human and physical resources at existing public hospitals are required to reduce deaths from acute abdominal conditions in India. Had all of the Indian population had access to well-resourced hospitals within 50 km, more than 50 000 deaths from acute abdominal conditions could have been averted in 2010, and likely more from other emergency surgical conditions. Our geocoded facility data were limited to public district hospitals. However, noting the high rate of catastrophic health expenditures in India, we chose to focus on publicly provided services which are the only option usually available to the poor. Funding: The Bill & Melinda Gates Foundation, Dalla Lana School of Public Health, and Canadian Institute of Health Research.